2011
DOI: 10.1038/hr.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedforward control of body fluid homeostasis by hepatorenal reflex

Abstract: The liver, well known for its role in metabolism, clearance and storage can also be regarded as a sensory organ. The liver is an ideal place to monitor the quality and quantity of absorbed substances, because portal blood delivers substances absorbed from the intestine to the liver and these substances circulate in the hepatic vasculature before substances enter the systemic circulation. Sodium (Na + )-sensitive mechanism exists in the liver; it is stimulated by the increase in Na + concentration in the portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Studies have shown that the infusion of water into the portal vein results in greater urinary excretion than infusing the same volume of water into the vena cava, a finding also supported by earlier work (2, 62, 66). These findings highlight another powerful mechanism for maintaining fluid homeostasis, which is known as the hepatorenal reflex.…”
Section: Hepatic Afferent Nervessupporting
confidence: 74%
See 3 more Smart Citations
“…Studies have shown that the infusion of water into the portal vein results in greater urinary excretion than infusing the same volume of water into the vena cava, a finding also supported by earlier work (2, 62, 66). These findings highlight another powerful mechanism for maintaining fluid homeostasis, which is known as the hepatorenal reflex.…”
Section: Hepatic Afferent Nervessupporting
confidence: 74%
“…Similar to osmoreception, the hepatic nervous system recognizes changes in ion concentration before they occur in the systemic blood (63). Hepatic nerves have a distinct advantage for the detection of ions compared to other organs since the concentration of absorbed substances in the portal vein is 4–5 times higher than that detected in the systemic blood (62). Thus, the liver is an ideal “predictor” of systemic blood-ion concentration, allowing for predictive compensation of fluid homeostasis.…”
Section: Hepatic Afferent Nervesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not detect liver morphological or functional abnormalities, it is possible that the liver ACE modulates hepatorenal reflexes in the ACE 3/3 mice. While work by others highlights the importance of these reflexes in the regulation of postprandial natriuresis, such a mechanism seems to be less important for longterm sodium homeostasis (39).…”
Section: Figurementioning
confidence: 99%